Efek Diet Tinggi Protein, Rendah Karbohidrat, Rendah Lemak pada Tikus Wistar Jantan terhadap Perubahan Berat Badan, Kadar Glukosa dan Kolesterol - Nur Upik En Masrika; Aryadi Arsyad; Ika Yustisia; Yulia Yusrini Djabir (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
One of the most popular diets today recommends a high protein- low carbohydrate diet as a weight loss strategy in obese patients. Diets high in protein appear to reduce appetite, energy intake, weight gain, and fat accumulation. The application of a high-protein diet has an impact on reducing the portion of other macronutrients, namely carbohydrates and fats. The purpose of this study was to determine the effect of a high protein, low carbohydrate and low fat (TPRKRL) diet on body health. With the focus of the analysis on changes in body weight, serum glucose and cholesterol levels in 22 male Wistar rat samples who were given the standard diet and the TPRKRL diet for 8 weeks. The results showed that there were no significant differences in the variables of body weight, serum glucose and cholesterol levels between the TPRKRL diet group and the control group (standard diet). In fact, the rats in the TPRKRL group experienced a relatively constant increase in body weight and glucose and cholesterol levels were susceptible to normal.Keywords: high protein; body weight; glucose; cholesterol